Optimization and device application potential of oxide–metal–oxide transparent electrode structure1. Issue 80 (2nd September 2015) - Kim, Yun Cheol; Lee, Su Jeong; Jung, Hanearl; Park, Bo-Eun; Kim, Hyungjun; Lee, Woong; Myoung, Jae-Min
<x xml:space="preserve">Abstract</x> Schematic illustration showing the layout of a fully transparent a-IGZO TFTs and the optical image of the a-IGZO TFT with the OMO electrodes on a 10 × 10 cm2 glass substrate.